Análise de econometria de dois sistemas naturais de tratamento de água residuária na suinocultura - Jasper, Samir Paulo [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP]; Biaggioni, Marco Antonio Martin [UNESP]; Oliveira, Eduardo Luiz de [UNESP]; Guerra, Saulo Philipe Sebastião [UNESP] (My University, 2008)
The aim of this work was to develop a detailed econometric analysis to compare a constructed wetland system - combined model, and a waste stabilization pond system - facultative pond, as a function of six different sizes of finishing pig farms and two waste management systems - wet and dry. The constructed wetland system using dried waste management showed the best economic results. This finding is due to the low-cost implementation a year both per animal and per kilogram of meat. This system also required the smallest area for waste treatment. The use of stabilization pond with wet waste management system showed a lower implementation cost a year per animal and per kilogram of meat, but it required large areas. The econometric analysis of both systems of wastewater treatment revealed an economy of scale.
Econometric analysis of two natural pig waste water treatment systems
Keywords: Constructed wetland; Econometric analysis; Stabilization pond; constructed wetland; econometrics; economy of scale; livestock farming; waste treatment; Animalia; Suidae